Memória, imaginário e representação em "A espantosa ode a São Francisco de Assis", de Vinícius de Moraes - Gonçalves, Juliany Paiva Costa de Sene (2014)
The poet is a "product" of a socio-cultural imaginary that often manages to subtly humanize the sacred element. Vinicius de Moraes "A espantosa ode a São Francisco de Assis" exemplifies that with its set of references from the social imaginary and the Catholic representation. More than a theme, its 138 lines pose a way of representing the sacred symbol by using the poetic discourse to make it human. Here is the subject matter of the research this dissertation presents, which aimed to analyze this poet work compared to the originality of Saint Francisco de Assis attitudes and points of view towards the sacred world as well as to see if the poet presents the exclusion, acceptance or non-acceptance of Catholic Church s conventional signs. To deal with symbols and representations as analytical categories, this study relied on the methodological support of cultural history, on the critical and analytical support of the phenomenology of the imaginary, and on the analytical support of literary criticism on Vinicius de Moraes. Such theoretical and methodological approach supports the analysis of the poem, which points out the existence of representations of such saint in artistic languages such as painting and poetry. In the written representation, Moraes poetry operates between two worlds: the saint one and the human one. Humanity and sanctity merge into a single being: the poet, whose voice translates it into a voice of a man who seeks to understand his existential crisis. Studying this poet s life and cultural, social e political universe showed that they may reveal his designs as a human being as well.